CD44 glycovaccine for bladder cancer: synthesis, pre-clinical validation and biotechnological solution thereof - Ferreira, Eduardo da Silva (2022)
Bladder cancer (BC) is the most common malignancy of the urinary tract, with high recurrence rates. Aberrant glycosylation of the proteins and lipids of the bladder cancer cells leads to the generation of truncated O-glycans, which have been linked to tumour progression and poor prognosis. Although truncated O-glycans, such as Tn and STn, are overexpressed in several carcinomas, they are also present in non-malignant disorders and, thus, challenge the development of targeted cancer immunotherapies. Therefore, we propose glycoproteome as a strategy to achieve cancer-specific structures for novel therapeutic treatments. Following this alignment, CD44s was associated with invasion and worst prognosis and the study of CD44s O-glycoforms, such as CD44s-Tn/STn may allow to overcome the lack of cancer specificity of CD44s. Accordingly, a glycovaccine based in glycopeptides CD44s-Tn/STn was generated by single-pot enzymatic synthesis, attending to induce an immune response against tumours CD44s-Tn/STn positive. Furthermore, the glycopeptides synthesized by us present equal glycosylation sites compared with bladder tumour cells, reinforcing the importance of glycovaccines in cancer treatment. The pre-clinical study demonstrates that glycoconjugated vaccine plus MPLA adjuvant do not cause cellular toxicity and it can generate humoral immune response. Despite these results indicating a promising strategy to improve cancer treatment, excessive costs associated with manufacturing remain a major drawback. Building on this, a lentiviral strategy was implemented to modify target cell lines in order to create genetically modified mammalian platforms for large-scale production of human glycopeptides. To conclude, this work established the molecular bases for the development of a well characterized multivalent glycovaccines aiming to improve anti-cancer immunotherapies settings.